2017
DOI: 10.1051/0004-6361/201731198
|View full text |Cite
|
Sign up to set email alerts
|

Ionized gas in the Scutum spiral arm as traced in [N ii] and [C ii]

Abstract: Context. The warm ionized medium (WIM) occupies a significant fraction of the Galactic disk. Determining the WIM properties at the leading edge of spiral arms is important for understanding its dynamics and cloud formation. Aims. To derive the properties of the WIM at the inner edge of the Scutum arm tangency, which is a unique location in which to disentangle the WIM from other components, using the ionized gas tracers C + and N + . Methods. We use high spectral resolution [C ii] 158 µm and [N ii] 205 µm fine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Hence, the spiral arm detection by means of RM observations in our Milky Way model is mostly a consequence of the increase in magnetic field strength within the arms. We note that this particular aspect of our MHD model may not accurately represent the Milky Way where the density of free electrons n el is also found to be higher within the arms (see, e.g., Cordes & Lazio 2002;Langer et al 2017). Thus, the RM signal in the Milky Way may be much more influenced by electron fractions than in our synthetic observations suggest.…”
Section: The Origin Of the Rm Signalmentioning
confidence: 73%
“…Hence, the spiral arm detection by means of RM observations in our Milky Way model is mostly a consequence of the increase in magnetic field strength within the arms. We note that this particular aspect of our MHD model may not accurately represent the Milky Way where the density of free electrons n el is also found to be higher within the arms (see, e.g., Cordes & Lazio 2002;Langer et al 2017). Thus, the RM signal in the Milky Way may be much more influenced by electron fractions than in our synthetic observations suggest.…”
Section: The Origin Of the Rm Signalmentioning
confidence: 73%
“…The presence of dense highly ionized gas, as derived from [N II], is an indication that the edge of the neutral gas does not transition rapidly to the low density WIM. Langer et al (2017) have argued, based on [N II] and [C II] observations of the Scutum arm tangency, that the dense ionized gas is a result of the compression of the WIM as it falls into the gravitational well of the spiral arm. The widespread distribution of dense highly ionized gas in the Goldsmith et al (2015)…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Goldsmith et al (2015) and Langer et al (2016) found that a significant fraction of the [C II], of order 20%-30%, comes from highly ionized dense gas. A related study of the Scutum spiral arm tangency found that [N II] 205 µm emission arose from two components, a low density, n(e) ∼ 0.9 cm −3 , compressed WIM at the arm-interarm interface and from high density, n(e) ∼ 30 cm −3 , ionized gas associated with the molecular clouds deep in the arm (Langer et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the Herschel Galactic [N ii] sparse survey, ten lines of sight observed with PACS were also observed with spectrally resolved 205 µm emission with Herschel's Heterodyne Instrument in the Far-Infrared (HIFI) and found to have ∼ 20 distinct velocity components (Langer et al 2016). Pineda et al (2019) analyzed the electron abundance and column density of N + in these 20 spectral components along with one in the Scutum arm l ∼30 • that had been observed in [N ii] 205 µm with SOFIA GREAT (Langer et al 2017). To derive the electron density, in the absence of spectrally resolved 122 µm [N ii] emission, Pineda et al (2019) developed a technique combining spectrally resolved Hnα radio recombination lines (RRLs) with the spectrally resolved [N ii] 205 µm line.…”
Section: Introductionmentioning
confidence: 99%